The Relationship between Interpersonal Anger and Religiosity: A Quantitative Study on Drivers - Duran, Mehmet Emrullah (Fırat University, 2024)
The main aim of the present study is to examine the relationship between interpersonal anger and religiosity among drivers. The study was conducted in February 2024. The sample of the study was composed of 265 drivers who are working in Konya. Within the scope of the purpose of the research, the relational screening model was used. The data was collected by questionnaire, which included Personal Information Form, Interpersonal Anger Scale, and Religious Attitude Scale. Perason Correlation Analysis and T Test were used in data analysis. As a result of the research, it was determined that the relationship between interpersonal anger and religiosity was negative, strong and statistically significant, and that interpersonal anger decreased as religiosity scores increased. It was determined that the relationship between the sub-dimensions of interpersonal anger, namely revenge reactions, passive-aggressive reactions, introvert reactions and indifferent reactions, and the sub-dimensions of religiosity, cognition, emotion, behavior and relationship, was strongly negative and statistically significant. It was found that the drivers' interpersonal anger and religiosity scores showed statistically significant differences according to the age variable. In addition, it was determined that the interpersonal anger score showed a statistically significant difference according to the nature of the vehicle variable.

Bu araştırmada, şoförlerin kişilerarası öfke ve dindarlık düzeyleri arasındaki ilişki incelenmiştir. 2024’ün Şubat ayında gerçekleştirilen araştırmaya Konya’da çalışmakta olan 265 şoför katılmıştır. Araştırmanın amacı kapsamında ilişkisel tarama modeli kullanılmıştır. Araştırma verileri anket tekniğiyle toplanmış ve anket formunda Kişisel Bilgi Formu, Kişilerarası Öfke Ölçeği ve Dini Tutum Ölçeği kullanılmıştır. Veri analizinde Perason Korelasyon Analizi ve T Testi kullanılmıştır. Araştırma sonucunda kişilerarası öfke ile dindarlık arasındaki ilişkinin negatif yönde güçlü düzeyde ve istatistiksel olarak anlamlı olduğu, dindarlık puanları yükseldikçe kişilerarası öfkenin azaldığı tespit edilmiştir. Kişilerarası öfkenin alt boyutları olan intikam tepkileri, pasif agresif tepkiler, içe dönük tepkiler ve umursamaz tepkiler ile dindarlığın alt boyutları biliş, duygu, davranış ve ilişki arasındaki ilişkinin negatif yönde güçlü düzeyde ve istatistiksel olarak anlamlı olduğu saptanmıştır. Şoförlerin kişilerarası öfke ve dindarlık puanlarının yaş değişkenine göre istatistiksel olarak anlamlı farklılık gösterdiği bulgusuna ulaşılmıştır. Ayrıca kişilerarası öfke puanının aracın niteliği değişkenine göre istatistiksel olarak anlamlı farklılık gösterdiği tespit edilmiştir.
KİŞİLERARASI ÖFKE VE DİNDARLIK İLİŞKİSİ: ŞOFÖRLER ÜZERİNE NİCEL BİR ARAŞTIRMA
Keywords: Social Work (Other); Sosyal Hizmetler (Diğer)